Relative localization estimation for multiple robots via the rotating ultra-wideband tag - Liu, Jinxin (2023)
Most distributed algorithms for robot coordination require relative location information, but how to obtain relative locations in a distributed manner is still a primary problem to address in multi-robot applications. In order to obtain the relative locations between robots, no matter whether they are in relative motion or stationary situation, we design a rotating ultra-wideband tag to provide the persistency of excitation condition and two estimation algorithms to estimate the relative locations in a distributed manner. Moreover, our approach relies only on on-board sensors and requires only one ultra-wideband tag per robot, eliminating the need for any ground anchors, thus allowing deployment in GNSS-denied environments without range restrictions. The proposed approach in this letter is also tested in simulations and experiments to verify the theoretical findings and effectiveness in practice.